2006
DOI: 10.1063/1.2354333
|View full text |Cite
|
Sign up to set email alerts
|

Explicit solutions for N-dimensional Schrödinger equations with position-dependent mass

Abstract: With the consideration of spherical symmetry for the potential and mass function, one-dimensional solutions of non-relativistic Schrödinger equations with spatially varying effective mass are successfully extended to arbitrary dimensions within the frame of recently developed elegant nonperturbative technique, where the BenDaniel-Duke effective Hamiltonian in one-dimension is assumed like the unperturbed piece, leading to wellknown solutions, whereas the modification term due to possible use of other effective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…According to recent contributions [70,440,441], it is shown that the positiondependent effective mass Schrödinger equation with physical potentials is given by Based on the following formula…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent contributions [70,440,441], it is shown that the positiondependent effective mass Schrödinger equation with physical potentials is given by Based on the following formula…”
Section: Formalismmentioning
confidence: 99%
“…Except for these, the higher dimensional Schrödinger equation are also concerned with the following scattered fields such as the position and momentum information entropies of the D-dimensional harmonic oscillator and hydrogen atom [58], the Fermi pseudo-potential in arbitrary dimensions [59], the uncertainty relation for Fisher information of D-dimensional single-particle systems with central po-tentials [60], the dimensional expansion for the Ising limit of quantum field theory [61], the scalar Casimir effect for an N -dimensional sphere [62], the multidimensional extension of a WKB improvement for the spherical quantum billiard zeta functions [63], the study of bound states in continuous D dimensions [64], the suppersymmetry and relationship between a class of singular potentials in arbitrary dimensions [65], the bound states and resonances for "sombrero" potential in arbitrary dimensions [66], the renormalization of the inverse squared potential in D dimensions [67], the generalized coherent states for the d-dimensional Coulomb problem [68], the quantum particles trapped in a position-dependent mass barrier [69,70], the harmonic oscillator in arbitrary dimensions with minimal length uncertainty relations [71], the stable hydrogen atom in higher dimensions [72], the relation between dimension and angular momentum for radially symmetric potential in Ddimensional space [73], the D-dimensional hydrogenic systems in position and momentum spaces [74], the first-order intertwining operators and position-dependent mass Schrödinger equation in d dimensions [75], intertwined isospectral potentials in arbitrary dimensions [76], convergent iterative solutions for a sombrero-shaped potential in any space dimension and arbitrary angular momentum [77].…”
Section: Introduction 1 Basic Reviewmentioning
confidence: 99%
“…Although mostly one-dimensional equations have been considered up to now, several works have recently paid attention to d-dimensional problems [7,17,18,19,20,21,22]. In [7] (henceforth referred to as I and whose equations will be quoted by their number preceded by I), we have analyzed d-dimensional PDM Schrödinger equations in the framework of first-order intertwining operators and shown that with a pair (H, H 1 ) of intertwined Hamiltonians we can associate another pair (R, R 1 ) of second-order partial differential operators related to the same intertwining operator and such that H (resp.…”
Section: Introductionmentioning
confidence: 99%
“…Oyewumi et al [19] studied the N-dimensional Pseudoharmonic oscillator. Gönül and Koçak [20] investigated explicit solutions for N-dimensional Schrödinger equations with position-dependent mass. The N-dimensional Kratzer-Fues potential was discussed by Oyewumi [21], Ikhdair and Sever [22], studied the modi-fied Kratzer-Fues potential plus the ring shape potential in D-dimensions while Dong [23], reviewed the wave equations in higher dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Oyewumi et al [19] studied the N-dimensional Pseudoharmonic oscillator. Gönül and Koçak [20] investigated explicit solutions for N-dimensional Schrödinger equations with position-dependent mass. The N-dimensional Kratzer-Fues potential was discussed by Oyewumi [21],…”
Section: Introductionmentioning
confidence: 99%